A Case of Ischemic Duodenitis Associated with Superior Mesenteric Artery Syndrome Caused by an Abdominal Aortic Aneurysm - Yusuke Okuyama; Takumi Kawakami; Haruki Ito; Hirotomo Otsuka; Yasuyuki Enoki; Masahito Nishimura; Norimasa Yoshida; Sotaro Fujimoto (Case Reports in Gastroenterology, 2011)
A 74-year-old woman was admitted to our hospital with upper abdominal pain and bloody vomiting. An abdominal aneurysm compressed the third portion of the duodenum and the second portion of duodenum was distended with thickened walls as in superior mesenteric artery syndrome. Endoscopic examination showed an edematous mucosa with hemorrhagic erosions, shallow longitudinal ulcers, and star-shaped ulcers in the duodenum. We diagnosed this case as ischemic duodenitis associated with superior mesenteric artery syndrome caused by compression by an abdominal aortic aneurysm. The symptoms improved on treatment with bowel rest, total parenteral nutrition and administration of a proton pump inhibitor. We present here a rare case of ischemic duodenitis and summarize the previous medical literature on the disease.